Incentives for managers and inequality among workers: evidence from a firm level experiment - Oriana Bandiera; Iwan Barankay; Imran Rasul (Institute for the Study of Labor (IZA), 2006)
We present evidence from a firm level experiment in which we engineered an exogenous change in managerial compensation from fixed wages to performance pay based on the average productivity of lower-tier workers. Theory suggests that managerial incentives affect both the mean and dispersion of workers' productivity through two channels. First, managers respond to incentives by targeting their efforts towards more able workers, implying that both the mean and the dispersion increase. Second, managers select out the least able workers, implying that the mean increases but the dispersion may decrease. In our field experiment we find that the introduction of managerial performance pay raises both the mean and dispersion of worker productivity. Analysis of individual level productivity data shows that managers target their effort towards high ability workers, and the least able workers are less likely to be selected into employment. These results highlight the interplay between the provision of managerial incentives and earnings inequality among lower-tier workers.
Keywords: J33; M52; 330; managerial incentives; targeting; selection; earnings inequality; Vergütungssystem; Management; Erfolgsbeteiligung; Ungelernte Arbeitskräfte; Arbeitsproduktivität; Lohndifferenzierung; Großbritannien